Modern marvels Architectural wonders. Mount Rushmore ; Hoover Dam (New York A&E Television Networks Marketed and distributed in the U.S. by New Video Group, 2007)
This program circles the globe to profile the world's most phenomenal architectural gems: Baseball Parks, the Egyptian Pyramids, the Eiffel Tower and much more!
Originally aired on the History Channel.
DVD.
Keywords: Engineering design -- United States; Dams -- United States -- Design and construction; Mount Rushmore National Memorial (S.D.).; Hoover Dam (Ariz. and Nev.) -- History